O TUTOR E A TUTORIA EM EDUCAÇÃO A DISTÂNCIA (EAD): O QUE NOS DIZEM AS DISSERTAÇÕES E TESES BRASILEIRAS EM UMA DÉCADA (2005 A 2015) DE PRODUÇÃO ACADÊMICA? / The tutor and tutoring in distance education (EaD): What do tell us dissertations and Brazilian theses in a decade (2005 to 2015) of academic production? (Trabalho & Educação, 2018)
The field of education has been called to respond to the demands imposed by the transformations in all spheres of social life since the intensification of the use of Digital Technologies of Information and Communication (TDIC's). In this scenario, Distance Learning (EaD) and its protagonists in the teaching-learning process stand out, among which the tutor stands out. In this sense, the present research aimed to identify and examine the research perspectives, as well as the main theoretical and methodological fields present in Brazilian theses and dissertations from the period 2005 to 2015 that deal with tutoring in EaD. Considering the nature of the problem of this study, we opted for a bibliographical and documentary research, predominantly qualitative, but without contempt for quantitative methods. In documentary research, we have focused on what laws, decrees, and ordinances have pointed out as perspectives for EaD in Brazil. In the bibliographic research, in addition to the reading of authors who have excelled in studies on tutoring, teaching and distance education - Belloni, Mill, Tardif and Lessard, Brezezinski, Maggio, Bernal, Preti, Toschi, Lapa and Pretto, among others - we analyzed the theses and dissertations selected in the portals CAPES and BDTD/IBICT, considering the period 2005-2015. As an analysis procedure we opted for the adaptation of the Bardin Content Analysis technique (1977), based on the reading of the abstracts of the selected papers. Our results point out, besides the difficulties in working with theses and dissertation banks, how complex is the field of discussion about EAD tutoring, permeated by divergent positions and many contradictory aspects. The controversies that the term "tutor / mentoring" engender, especially when discussed in their relationship with teaching, became evident. In general, it is highlighted as a challenging perspective the resignification of teaching as collective work, in which the tutor appears as the most devalued. The research perspectives highlighted in the analyzed theses and dissertations also confirm the centrality of the role of the tutor in the teaching proposals in EaD, in which he is the main responsible for the process of pedagogical mediation, which should happen in an integrated and collaborative way in virtual environments of learning, permeated by the aid of technological tools and contributing to the formation of an autonomous, critical and reflective student. The training in the specificities of the EAD modality appears as essential and has occurred mostly inefficiently according to the works analyzed. We believe that few studies have demonstrated more detailed research perspectives, with a better theoretical and methodological framework. We found little exploration of some significant research perspectives for teaching distance education, such as the convergence of face-to-face and distance learning, adult education (andragogy) and the perspective of Special and Inclusive Education. We hope that from this study further investigations can be made, offering elements for the construction of new understandings and knowledge in the field of the Brazilian EaD.___O campo da educação vem sendo chamado a responder às exigências impostas pelas transformações em todos os âmbitos da vida social desde a intensificação do uso das Tecnologias Digitais da Informação e Comunicação (TDIC’s). Nesse cenário ganha destaque o Ensino a Distância (EaD) e os seus protagonistas no processo de ensino-aprendizagem, dentre os quais sobressai-se o tutor. Nesse sentido, a presente pesquisa teve por objetivo identificar e examinar as perspectivas de investigação, bem como os principais campos teórico-metodológicos presentes nas dissertações e teses brasileiras do período de 2005 a 2015 que versam sobre a tutoria na EaD. Tendo em vista a natureza do problema deste estudo, optamos pela realização de uma pesquisa bibliográfica e documental, predominantemente qualitativa, mas sem desprezo pelos métodos quantitativos. Na pesquisa documental nos detivemos àquilo que leis, decretos e portarias têm apontado como perspectivas para a EaD no Brasil. Na pesquisa bibliográfica, além da leitura de autores que têm se destacado em estudos sobre tutoria, trabalho docente e educação a distância – Belloni, Mill, Tardif e Lessard, Brezezinski, Maggio, Bernal, Preti, Toschi, Lapa e Pretto, dentre outros – analisamos as dissertações e teses selecionadas nos portais CAPES e BDTD/IBICT, considerando o período 2005-2015. Como procedimento de análise optamos pela adaptação da técnica de Análise do Conteúdo de Bardin (1977), a partir da leitura dos resumos dos trabalhos selecionados. Nossos resultados ressaltam, além das dificuldades no trabalho com bancos de dissertações e teses, o quão complexo é o campo de discussão sobre a tutoria na EaD, permeado por posições divergentes, além de  muitos aspectos contraditórios. Ficaram evidentes as controvérsias que o termo “tutor/tutoria” engendra, sobretudo quando discutido nas suas relações com a docência. De um modo geral, destaca-se como perspectiva desafiadora a ressignificação da docência como trabalho coletivo, no qual o tutor aparece como o mais desvalorizado. As perspectivas de investigação em destaque nas dissertações e teses analisadas confirmam ainda a centralidade do papel do tutor nas propostas de ensino em EaD, nas quais figura como o grande responsável pelo processo de mediação pedagógica, que deve acontecer de forma interativa e colaborativa nos ambientes virtuais de aprendizagem, permeado pelo auxílio de ferramentas tecnológicas e contribuindo para a formação de um estudante autônomo, crítico e reflexivo. A formação nas especificidades da modalidade EaD aparece como imprescindível e tem ocorrido majoritariamente de forma ineficiente segundo os trabalhos analisados. Consideramos que poucos trabalhos demonstraram perspectivas de investigação mais aprofundadas, com referencial teórico-metodológico melhor delineado. Pareceu-nos pouco exploradas algumas perspectivas de investigação significativas para se pensar a tutoria na EaD, tais como a convergência dos modelos presencial e a distância, a educação de adultos (andragogia) e a perspectiva da Educação Especial e Inclusiva. Esperamos que a partir deste estudo investigações mais aprofundadas possam ser feitas, oferecendo elementos para a construção de novas compreensões e conhecimentos no campo da EaD brasileira.